Figurões da terra : trajetórias e projetos políticos no Espírito Santo de oitocentos - Goularte, Rodrigo da Silva (2008)
As fruit of the decentralization politics promoted for the Additional Act of 1834 all the Brazilian provinces had been able to install a State legislature. In the case of the Espirito Santo, this work defends the hypothesis of that the individuals that had occupied the regional parliament had in its pasts professional careers and politics that had conferred them training and knowledge of the regional and national reality, making possible to play them its roles while provincial members of the house of representatives. The trajectories politics had been made inside of the administrative pictures of the province. Professionally the members of the house of representatives of 1835 had been involved in three careers: the military, the ecclesiastic and the civil bureaucracy. The capital politician promoted for these trajectories allowed them to remain in the scene provincial politician until middle of the XIX and to take care of many of the regional demands.